Management of Parshnishool (Heel Pain) Due to Vatakantaka (Calcaneal Spur) With Agnikarma (Therapeutic Burn). – A Case Report.: Life Sciences -Ayurveda - Jadhav, Divya; Deshpande, Mayuri Amol; Deshpande, Amol Madhav; Urkude, Minakshi (International Journal of Life Science and Pharma Research, 2023)
Pain is the commonest symptom due to which patients come to the Physician. Every patient wants instant relief from such type ofunwanted feelings. Conventional therapies have many painkillers that instantly give the desired effect with a byproduct of many side effects.Parshnishool (Heel pain) occurring due to Vatakantaka (calcaneal spur) is a common type of pain nowadays. It hampers day-to-day life choresaffecting the physical as well as mental status of an individual. Ayurveda has solutions for all types of diseases occurring in every Era. Thecalcaneum has tiny osteophyte projections known as calcaneal spurs. It is not an acute illness with abrupt onset. It takes place as a result ofprogressive changes in that area. Calcaneal spurs are often seen in two regions: the inferior and posterior ones. The lower one is placed onthe calcaneum's inferior side and frequently reacts to plantar fasciitis over time. Calcaneal spur and its symptoms can be easily treated withAgnikarma means therapeutic heat application. Vata is the causative factor in all types of pain. There are a total of 80 diseases that occur due tothe vitiation of Vata. Vata and Agni have exactly opposite properties. In this case, we use Loha shalaka (Iron lancet) for therapeutic burns. Lohashalaka gives more relief from pain than any other shalakas. The patient got complete relief after three sittings. He was advised with someinternal medication as supplements. Agnikarma is the easy, less time-consuming, and financially affordable treatment in Pashnishool occurring inVatakantaka with no side effects.